PERCEPTIONS ABOUT THE ROLE OF RELIGION IN ENSURING PEACE IN GHANA’S BODY POLITY: A CASE STUDY OF GHANA’S POLITICAL PARTY FUNCTIONARIES - Raphael Avornyo (European Scientific Journal, ESJ, 2013)
After experiencing massive social, political and economic upheavals in Ghana between 1966 and 1992, Ghana ushered in constitutional democracy in 1992. Since that period, the country, compared with her neighbours, has been enjoying relative political stability. Prior to adopting the Western type of democracy, after gaining independence in 1957, religion played a significant role in ensuring peace and stability of the body polity. The question that this paper sought to find an answer to is: Do modern-day Ghanaian politicians exercise their political authority based on their religious beliefs and practices like in the past, thereby ensuring peace? Using the country’s functionaries of political parties as a case study, the paper sought to answer the question above. Data for the study were collected using both survey questionnaire and in-depth interview from 44 functionaries of political parties through purposive sampling. Both qualitative and quantitative methods were used. Findings from the study were analysed using the Statistical Product for Social Services (SPSS). The positions of Habermas, Rawls and their critics regarding the role of religion in the public sphere formed the theoretical framework for the study. It is the thinking of this paper that, like in the past, opinion leaders, including politicians, should exercise their authority based on their religious convictions, since this would contribute to peace and development.